Pengaruh Good Corporate Governance dan Budaya Tri Hita Karana Pada Kinerja Bank Perkreditan Rakyat - Dwija Putri, I Gusti Ayu Made Asri; Ulupui, I.G.K.A; Wirawati, Ni Gusti Putu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 12 No 1 (2017)DO - 10.24843/JIAB.2017.v12.i01.p03, 2017)
The purpose of this study, namely to obtain empirical evidence that the implementation of corporate governance affect the performance of “Bank Perkreditan Rakyat” ( rural banks), and the role of local culture “Tri Hita Karana “to the BPR’s performance. The population is all BPR located in Badung and Denpasar. The samples using purposive sampling method. The data in this study were collected using a questionnaire are distributed directly to the object of research. “BPR” number into the sample in this study was 65 Banks. Data analyzed by model Multiple Regression Analysis. The research result show that the principles of corporate governance and the local cultural effect on the performance of BPR in Badung and Denpasar. “Bank Perkreditan Rakyat”. The implication of the study is important for the government to solve the economic problem using Corporate Governance and Tri Hita Karana concept.
Keywords: Good Corporate Governance, budaya lokal, dan kinerja